Surface decorated Ni sites for superior photocatalytic hydrogen production - Huang, Wenhuan; Bo, Tingting; Zuo, Shouwei; Wang, Yunzhi; Chen, Jiamin; Ould‐Chikh, Samy; Li, Yang; Zhou, Wei; Zhang, Jing; Zhang, Huabin (SusMat (Online), 2022)
Precise construction of isolated reactive centers on semiconductors with well‐controlled configurations affords a great opportunity to investigate the reaction mechanisms in the photocatalytic process and realize the targeted conversion of solar energy to steer the charge kinetics for hydrogen evolution. In the current research, we decorated isolated Ni atoms on the surface of CdS nanowires for efficient photocatalytic hydrogen production. X‐ray absorption fine structure investigations clearly demonstrate the atomical dispersion of Ni sites on the surface of CdS nanowires. Experimental investigations reveal that the isolated Ni atoms not only perform well as the real reactive centers but also greatly accelerate the electron transfer via direct Ni–S coordination. Theoretical simulation further documents that the hydrogen adsorption process has also been enhanced over the semi‐coordinated Ni centers through electronic coupling at the atomic scale. The precise construction of isolated reactive centers on semiconductors with well‐controlled configurations affords a great opportunity to investigate the reaction mechanisms in the photocatalytic process. In the current research, Ni atom‐decorated CdS nanowires have been well investigated for photocatalytic hydrogen evolution. The energy transfer routine is well elaborated, while the Ni sites have been demonstrated to be the real active centers for the hydrogen evolution reaction.